Biochemical, mutational and in silico structural evidence for a functional dimeric form of the ornithine decarboxylase from Entamoeba histolytica. - Preeti; Satya Tapas; Pravindra Kumar; Rentala Madhubala; Shailly Tomar (Public Library of Science (PLoS), 2012)
BACKGROUND: Entamoeba histolytica is responsible for causing amoebiasis. Polyamine biosynthesis pathway enzymes are potential drug targets in parasitic protozoan diseases. The first and rate-limiting step of this pathway is catalyzed by ornithine decarboxylase (ODC). ODC enzyme functions as an obligate dimer. However, partially purified ODC from E. histolytica (EhODC) is reported to exist in a pentameric state. METHODOLOGY AND RESULTS: In present study, the oligomeric state of EhODC was re-investigated. The enzyme was over-expressed in Escherichia coli and purified. Pure protein was used for determination of secondary structure content using circular dichroism spectroscopy. The percentages of α-helix, β-sheets and random coils in EhODC were estimated to be 39%, 25% and 36% respectively. Size-exclusion chromatography and mass spectrophotometry analysis revealed that EhODC enzyme exists in dimeric form. Further, computational model of EhODC dimer was generated. The homodimer contains two separate active sites at the dimer interface with Lys57 and Cys334 residues of opposite monomers contributing to each active site. Molecular dynamic simulations were performed and the dimeric structure was found to be very stable with RMSD value ∼0.327 nm. To gain insight into the functional role, the interface residues critical for dimerization and active site formation were identified and mutated. Mutation of Lys57Ala or Cys334Ala completely abolished enzyme activity. Interestingly, partial restoration of the enzyme activity was observed when inactive Lys57Ala and Cys334Ala mutants were mixed confirming that the dimer is the active form. Furthermore, Gly361Tyr and Lys157Ala mutations at the dimer interface were found to abolish the enzyme activity and destabilize the dimer. CONCLUSION: To our knowledge, this is the first report which demonstrates that EhODC is functional in the dimeric form. These findings and availability of 3D structure model of EhODC dimer opens up possibilities for alternate enzyme inhibition strategies by targeting the dimer disruption.